A STUDY ON NEPALESE STUDENTS IN SOUTH KOREA: PULL FACTORS, PROBLEMS, AND FUTURE PROSPECTS - SHRESTHA, MADHUKAR (Graduate School of International Studies Ajou University, 2017)
South Korea, the trend of accepting the international students was put into effect only after early 2000 and Nepalese students also started to arrive as international students in Korea during this period and Society of Nepalese Student in South Korea was formed in 2004. The literature review has showed that Nepalese student population in South Korea has a unique feature in comparison to Nepalese students going to other countries like Japan, Australia or USA as most of them are enrolled in graduate and Ph.D. level where as undergraduate students population is more on other countries. Furthermore international student population in Korea also shows that most of the students are enrolled in undergraduate or language courses. The major pull factors for students to come to Korea were due to the scholarship opportunity, for the research and specialization, to earn a foreign degree and low expense at the first as students. For the students who receive scholarship research and specialization is the main pull factor whereas for most of the self- financed students have agreed that they came to Korea to earn foreign degree. Along with this, the self- financed students have agreed that they come to Korea as the expense of coming to Korea in the very beginning as a student is cheaper. The students have agreed to all of the factors as the difficulties they have faced in Korea but ‘lack of part-time work’, ‘Visa extension procedures’ and ‘financing the studies’ was emphasized as strongly agreed difficulties by the self- financed students. Most of the Nepalese students do not see a future in Korea and students have responded to either ‘studying further outside South Korea’ or ‘return back to Nepal as their future plan. Korean government is although trying its best to make the country more open towards the foreign student by creating different scholarship and policies like “study Korea project 2020” but still the number of Nepalese students seem to be very less. The interest of Nepalese student towards Korea seems to be increasing but it still lags way behind in global market for the Nepalese student.
학위논문(석사)--아주대학교 국제대학원 :국제개발협력과,2017. 2
Keywords: Nepalese Students; South Korea; International Student; Pull and Push Factors; Problems faced